The effect of hydroxyapatite and growth factors on reparative dentine formation in the therapy of injured pulp - Veličković, Zorana; Živković, Dušan; Bubalo, Marija; Živković, Milan; Mitić, Aleksandar; Miladinović, Milan; Duka, Miloš; Lazić, Dragoslav (Vojnosanitetski pregled, 2021)
Background/Aim. The studies of hydroxyapatite (HAp) and growth factors as the materials used for direct pulp capping have produced conflicting results for both the issue of the inflammatory response and the issue of calcified bridge formation. Hap/poly (lactide-co-glycolide) (HAp/PLGA) is a bioresorbable polymer with demonstrated good characteristics as the carrier for the bone morphogenetic protein necessary in bone tissue regeneration. The role of growth factors in dental tissue reparation (in both reactionary and reparative dentinogenesis) represents the new foundation and provides a different approach to dental pulp treatment. Growth factors – transforming growth factor beta-1 (TGF-β-1) – directly induce morphological and functional differentiation of neo-odontoblasts. The aim of this study was to investigate the effect of calcium HAp/PLGA and growth factors (TGF β-1) in the formation of a calcified tissue – dentine bridge – on the teeth of our experimental model. Methods. In this experimental study, rodent (rabbit) teeth were used as the animal model. After the trepanation of pulp space with sterile steel drills, the pulp was capped with calcium HAp/PLGA (experimental group I; n = 60); calcium HAp/PLGA combined with TGF β-1 growth factor (experimental group II; n = 60), and there was a control group of intact teeth (n = 20). The experiment was performed in general anesthesia. The animals were kept alive for 1, 3, and 6 months. The extracted teeth were adequately prepared for scanning electron microscopy. Results. Scanning electron microscopy demonstrated that the number of teeth with calcified tissue in the form of dental bridges in the HAp/PLGA+TGF β-1 group, 6 months after the treatment, was statistically significantly greater (66.67%) than after 3 months (26.67%), at the statistical significance level of p
Keywords: dental pulp; dental pulp capping; dentine; rabbits; minerals